A Hybrid Method for Assigning Containers to AGVs in Container Terminal. Issue 3 (2016) - Zaghdoud, Radhia; Mesghouni, Khaled; Dutilleul, Simon Collart; Zidi, Kamel; Ghedira, Khaled
Abstract: The problem of loading and unloading ship containers can be decomposed in some sub problems such as storage problem, transportation problem, routing problem, assigning problem, etc… In this paper, we are interested to the assignment of containers to Auto guided vehicles (AGVs) problem. This problem includes three sub problems: routing problem and assignment problem and scheduling problem. We propose a hybrid approach to solve it; Dijkstra algorithm, Genetic algorithm (GA) and a heuristic method to choose the AGV for each container. A comparative study was made between three approaches; the first approach consists of applying the GA, the second one present hybridization between Dijkstra algorithm and GA and the third approach add to the second one the using of heuristic (hybrid method using Dijkstra algorithm, GA and heuristic). Some numerical examples and tests are presented to prove the efficiency of our proposed approach.